Affective Disposition, Thinking Styles, Neuroticism and Life Satisfaction (2012)
The way in which positive and negative affects are perceived may be associated with a distinct pattern of behaviors and attitudes. The aim of this study was to evaluate the relationship between various combinations of affections and gender along with tendencies towards neuroticism, rumination, reflection, and life satisfaction. The participants were 348 students, who answered the questionnaire in groups. The euphoric group showed the highest scores of life satisfaction and emotional stability, while the dysphoric group presented the lowest scores. The emotional and apathetic groups showed no significant differences in relation to life satisfaction, depression, anxiety and vulnerability. From these results, it can be assumed that positive affect can lessen the impact that negative affect has on the development of vulnerability and other psychopathological symptoms. Interventions based on positive affect increase might be efficient to prevent vulnerability.